I Fought a Good Fight : A History of the Lipan Apaches - Robinson, Sherry (Book collections on Project MUSE., 2013)
This history of the Lipan Apaches, from archeological evidence to the present, tells the story of some of the least known, least understood people in the Southwest. These plains buffalo hunters and traders were one of the first groups to acquire horses, and with this advantage they expanded from the Panhandle across Texas and into Coahuila. Around 1700, the Comanches began forcing Eastern Apaches from their haunts, but they didn't yield easily and from then on were the Comanches' stubborn enemies. For a small group, the Lipans had an outsized impact through three centuries.